Saw‐tooth modulation of the deep‐water thermohaline properties in the southern Adriatic Sea. Issue 7 (2nd July 2016) - Querin, Stefano; Bensi, Manuel; Cardin, Vanessa; Solidoro, Cosimo; Bacer, Sara; Mariotti, Laura; Stel, Fulvio; Malačič, Vlado
Abstract: In this study, we investigate the dynamics of the bottom layer of the southern Adriatic Sea (eastern Mediterranean basin) by merging experimental measurements and numerical simulations. We hypothesize that the recently observed continuous density decrease over time, which was basically related to a temperature increase, and the following sudden density rise, which was caused by the intrusion of very dense water masses (cold but relatively fresh), constitute one cycle of a general "saw‐tooth" pattern: the alternation of long‐lasting and almost linear density decreases (mixing phases) and sudden density increases (dense water intrusion phases). The model results, which provide a basin‐scale view of the process, corroborate this theory because they satisfactorily reproduced the observed oceanographic features. We describe the almost linear density decrease in terms of local mixing fostered by the advection of flow instabilities that originate from the large‐scale quasi‐permanent cyclonic circulation. Conversely, diffusive processes play a minor role in determining the bottom layer thermohaline variability. The interpretation of the experimental findings, supported by the numerical simulations, suggests that similar dynamics might be observed in other basins characterized by similar bathymetric and hydrodynamic features. Key Points: Local mixing fostered by flow instabilities induces long‐term, positive thermohaline trends in the bottom of the southern Adriatic Sea Only exceptional production and sinking of large amounts of very dense shelf water can cause drastic bottom water renewal The hypothesized saw‐tooth modulation of the deep‐water thermohaline properties could be observed in similar basins in the world ocean